Evaluation of the overall impact of antibiotics growth promoters on broiler health and productivity during the medication and withdrawal period. (23rd January 2019) - Hamid, H; Zhao, L H; Ma, G Y; Li, W X; Shi, H Q; Zhang, J Y; Ji, C; Ma, Q G
ABSTRACT: The effectiveness of some common combination of antibiotic growth promoters (AGP) on growth performance, gut health, and meat quality was evaluated during the medication and withdrawal period in broilers. A total of 540 male Arbor Acre broilers at 0 D of age were randomly assigned to 5 treatments, with 6 replicates of 18 chicks. Broilers received diets during the medication period (0 to 42 D) as follows: NC (control diet without AGP), EN (NC + enduracidin 8 ppm + colistin sulfate 8 ppm), BZ (NC + bacitracin zinc 40 ppm + colistin sulfate 8 ppm), CT (NC + chlortetracycline 50 ppm + colistin sulfate 8 ppm), and VG (NC + virginiamycin 20 ppm + colistin sulfate 8 ppm). Broilers were switched to the same finisher diet without AGP during the withdrawal period (43 to 49 D). The feed:gain ratio in EN, BZ, CT, and VG groups were significantly decreased by 0.07, 0.10, 0.06, and 0.05 during 0 to 42 D ( P < 0.05), but increased by 0.19 ( P > 0.05), 0.33 ( P > 0.05), 0.49 ( P < 0.05), and 0.69 ( P < 0.05) during the withdrawal period, respectively. The jejunum villus height (VH) increased in EN group ( P < 0.05) and crypt depth (CD) reduced in BZ, CT, and VG groups ( P < 0.05) at 42 D, while jejunum VH increased in EN and BZ groups ( P < 0.05) at 49 D compared to NC group ( P < 0.05). Meat quality detection at 49 D found all AGP groups with the higher cook loss of the breast muscle, while CT group with the higher cook loss of thigh muscle. Consequently, the overall effects of 4 AGP combinations in the whole period were not significant on growth performance. Their poor growth performance during the withdrawal period should be partly attributed to the falling off a cliff of most digestive enzyme activities from 42 to 49 D. Attention should be paid to the adverse effects of AGP supplementation on meat quality, especially cook loss.